(untitled) (Journal of Science and Engineering, 2026)
We designed a seismic monitoring system integrating Micro Electro-Mechanical Systems (MEMS) accelerometer sensors with a Raspberry Pi and Long-Range (LoRa) communication technology. The system aims to provide a cost-effective and flexible approach for studying ground motion at various locations, with applications in geological research and disaster preparedness. Two types of MEMS sensors were employed to measure ground acceleration in three components. The Raspberry Pi functions as the central processing unit, responsible for data acquisition, processing, and storage. The data is saved in ASCII format and transmitted wirelessly to the main monitoring station using LoRa modules. Calibration of the system is carried out on a 1D shake table to ensure measurement accuracy. Further performance validation is conducted by comparing the sensor outputs with a standard strong-motion seismometer (Mitsutoyo JEP-6A3-2) in both the time and frequency domains. Experimental results from ambient vibration measurements indicate that the MPU6050 sensor achieves a higher goodness of fit with the strong-motion seismometer as compared to the ADXL345. This highlights the importance of filtering and calibration in improving measurement precision. Despite the limitations, the proposed system offers a scalable and cost-effective solution for seismic data collection of seismic monitoring system.